2021
DOI: 10.1080/22221751.2021.1884004
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of CRF55_01B among HIV-1 strain and its connection with traffic development in China

Abstract: CRF55_01B is a relatively "young" HIV strain. At present, we do not know much about its transmission characteristics in China. So, to describe the transmission characteristics of CRF55_01B strain among provinces and HIV infected people, and to analyze the reasons for its rapid epidemic in China, a total of 1237 subjects infected with CRF55_01B from 31 provinces spanning a period of 12 years from 2007 to 2018 were enrolled in this study. By constructing a molecular network and Bayesian correlation analysis, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Our previous research showed that CRF55_01B spreads rapidly from MSM to heterosexual people, and this strain has been found in all provinces, forming transmission clusters in more than half of the provinces. Its rapid transmission may be related to the development of transportation and technology [24]. CRF07_BC-N also showed higher network access and interprovincial transmission rates.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous research showed that CRF55_01B spreads rapidly from MSM to heterosexual people, and this strain has been found in all provinces, forming transmission clusters in more than half of the provinces. Its rapid transmission may be related to the development of transportation and technology [24]. CRF07_BC-N also showed higher network access and interprovincial transmission rates.…”
Section: Discussionmentioning
confidence: 96%
“…Although the proportion of CRF55_01B infection in our cohort was small, most of them (10/11) were found to have drug resistance mutations. CRF55_01B is a newly identified CRF of HIV-1 that originated from China and may lead to a higher risk of transmission [22,23], suggesting that surveillance and prevention of CRF55_01B is needed to forestall the HIV epidemic. Surprisingly, sex (female) was found to be a risk factor for PDR mutation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As a new recombinant subtype formed by the recombination of CRF01_AE and subtype B, CRF55_01B prevalence increased exponentially from 2005 to 2009 after its origin in Shenzhen. One of the factors contributing to its rapid transmission was the spread of the virus to different PLADs in 2007, as mediated by the rapid development of the Beijing-Guangzhou and Beijing-Kowloon railways ( 8 ). Moreover, even though this particular subtype originated in homosexual males, it was transmitted among heterosexuals.…”
Section: Discussionmentioning
confidence: 99%